Reversion to virulence evaluation of a 9R vaccine strain of Salmonella enterica serovar gallinarum in commercial brown layers - Okamoto, AS [UNESP]; Menconi, A [UNESP]; Gonçalves, GAM; Rocha, TS [UNESP]; Andreatti Filho, RF [UNESP]; Savano, EN; Sesti, L (Fundação APINCO de Ciência e Tecnologia Avícolas, 2010)
The live vaccine Cevac S. Gallinarum, made from a rough strain of Salmonella enterica subspecies enterica serotype Gallinarum is used for preventing fowl typhoid, a disease that still causes considerable economic losses in countries with a developing poultry industry. The objective of this paper was to evaluate a possible reversion to virulence of the strain used in a vaccine in commercial brown layers. Only Salmonella-free chicks were utilized. One hundred twenty (120) 12-day-old Dekalb brown layers divided in two trials were used. The first trial had six groups of 15 birds each. Birds of group 1 were vaccinated with 10 doses of Cevac S. Gallinarum subcutaneously and 10 doses orally, in a total of 20 doses of vaccine. Then the birds of groups 2, 3, 4, and 5 received inocula that contained feces and a pool of organs with fragments of liver, heart, spleen, and cecal tonsils obtained from the immediately previous group. The second trial had three groups with 10 birds each. Birds in group 7 received inocula containing a pool of organs from birds of group 5 from trial 1, whilst the birds in group 8 were vaccinated subcutaneously with one dose of vaccine. Both trials included negative control groups (6 and 9). Throughout the experimental period, birds were monitored for reactions to the vaccination on the site of administration, clinical signs, and post-mortem lesions. In each passage, in addition to the birds euthanized to provide the inocula material, two birds from each group were euthanized for assessment of possible lesions, and their organs (liver, heart, spleen and cecal tonsils) were cultured in an attempt to isolate the vaccine strain. Except for one bird from group 1, that had a local reaction on the site of vaccination - a small vesicle with less that 0.5 mm that persisted until the third day post vaccination -, no other bird had any local reaction to the vaccine or any visible clinical alteration. Birds in group 8 did not present any reaction or clinical alteration because of the vaccine. We only managed to re-isolate the vaccine strain in the inocula made from organs of birds in group 1. We confirmed the isolation by means of biochemical tests, serology, and acriflavine agglutination test. All other cultures made from organs or feces, from all the other experimental groups did not show any growth of the vaccine strain or any other Salmonella serovar, suggesting that the vaccinated birds did not shed the SG9R vaccine strain. No bird presented any clinical symptoms or died during the trials, and no gross lesions were observed in the post-mortem examinations. Under the controlled conditions and time-frame of the present experiment, it was possible to conclude that the rough 9R strain of Salmonella Gallinarum present in the vaccine Cevac S. Gallinarum (Ceva Campinas Ltda. - Campinas, SP - Brazil) did not revert to virulence.
Keywords: 9R strain; fowl typhoid; reversion to virulence; Salmonella Gallinarum; SG9R vaccine